KFC in Vietnam: American fried chicken meets Asian rice bowl - LUI, Patricia (Institutional Knowledge at Singapore Management University, 2025)
In March 2024, KFC in Vietnam was closing in towards its goal of 100 new restaurants in the country by 2025. However, the company faced stiff competition from other fast-food chains like Lotteria and Jollibee, and price wars and frequent promotions dominated the competitive landscape. The other challenge was the preference of Vietnamese consumers, who favoured street food over fast food due to its lower cost, perceived health benefits, and local flavours. This made market entry and sustenance challenging for fast-food chains. Over the past decade, however, consumer preferences had started shifting, allowing such chains to grow market share, with KFC establishing itself as the second-largest fast-food group, following Lotteria. This growth was fueled by strategies such as adapting the menu with local flavours, enhancing customer experience, and strengthening its digital presence. By 2020, international fast-food chains held approximately 43.7% of Vietnam's food service market. Lotteria led with nearly 9% market share, followed by KFC at 8.5%. Despite the collective dominance of international brands, individual chains held relatively small shares due to the fragmented nature of the market. However, the prospects of the fast-food market were bright, and the market size was projected to exhibit a growth rate of 5.65% during 2024-2032. While some other fast-food players like McDonald’s and Burger King were less successful in the country, it was not evident if KFC would continue to dominate the market. Could KFC rapidly grow its market share and emerge victorious in Vietnam's fast-food race in a fiercely competitive market? The case helps students analyse market competition and competitive strategies, localisation strategies of global fast-food chains, and digitalisation strategies to compete in an evolving market. It also evaluates the ‘Franchisee’ business model, and its significance in the global expansion of fast food.